Study of Risk Factors in Children with Birth Asphyxia - Kumari, Mala; Soomro, Tufail Ahmed; Qureshi, Rizwana; Kamran, Bela; Qureshi, Mahnoor; Bai, Poonam (Biological and Clinical Sciences Research Journal, 2025)
Birth asphyxia is a significant contributor to neonatal morbidity and mortality in developing countries. Identifying modifiable maternal and perinatal risk factors can enable timely interventions to reduce the incidence of asphyxia-related complications in term newborns. Objective: To assess the association of various maternal and perinatal risk factors with birth asphyxia in term neonates admitted to a tertiary care hospital in Pakistan. Methods: A case-control study was conducted at the Department of Pediatrics, Ghulam Muhammad Mahar Medical College, Sukkur, from July 1, 2024, to December 31, 2024. A total of 62 term neonates were enrolled and divided into two groups: Group A (cases, n=31) with birth asphyxia and Group B (controls, n=31) without birth asphyxia. Neonates with congenital malformations, chromosomal anomalies, or low APGAR scores due to anesthesia were excluded. Data were collected using structured proformas and included maternal factors (parity, anemia, pregnancy-induced hypertension, chorioamnionitis, mode of delivery, cardiotocography findings) and neonatal parameters (birth weight, length, head circumference, and gender). Statistical analysis was conducted using SPSS v25. Chi-square test and t-test were applied; a p-value <0.05 was considered statistically significant. Results: The mean birth weight was 3.64 ± 0.53 kg in cases versus 3.71 ± 0.51 kg in controls, and the mean length was 48.81 ± 3.18 cm versus 50.11 ± 2.87 cm, respectively. Head circumference was nearly identical between groups. Cesarean section (58% vs. 35%), rural residence (64% vs. 90%), and primiparity (65% vs. 39%) were more frequent among cases. Statistically significant risk factors associated with birth asphyxia included meconium aspiration syndrome (36% vs. 13%; p=0.038), fetal distress (48% vs. 13%; p=0.002), and pregnancy-induced hypertension (42% vs. 7%; p=0.001). Other factors like prolonged labor, maternal anemia, and chorioamnionitis did not show significant association. Conclusion: This study identifies meconium aspiration syndrome, fetal distress, and pregnancy-induced hypertension as major risk factors associated with birth asphyxia in term neonates. These findings emphasize the importance of vigilant intrapartum monitoring and early maternal risk assessment to prevent asphyxia-related complications.